1996
DOI: 10.3346/jkms.1996.11.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Relations among traumatic subdural lesions

Abstract: Acute subdural hematoma (ASDH), chronic subdural hematoma (CSDH) and subdural hygroma (SDG) occur in the subdural space, usually after trauma. We tried to find a certain relationship among these three traumatic subdural lesions in 436 consecutive patients. We included all subdural lesions regardless of whether they were main or not. We evaluated the distribution, age incidence and interval from injury to diagnosis of these lesions, and the frequency of new subdural lesions in each lesion. ASDH constituted 68.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 0 publications
1
27
1
2
Order By: Relevance
“…Then the left side of the cranium would be the top, when a man lies on his back. CSDHs frequently originate from SDGs 13,15,20) . SDGs usually locate on the top of the head 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Then the left side of the cranium would be the top, when a man lies on his back. CSDHs frequently originate from SDGs 13,15,20) . SDGs usually locate on the top of the head 14) .…”
Section: Discussionmentioning
confidence: 99%
“…86,87 Therefore, it has been suggested that repeated microhemorrhages possibly convert an SDHy into an expanding cSDH. 33,50,52,57,66 These pathogenetic considerations show why it is important for the forensic expert to differentiate between cSDH and SDHy. While cSDHs appear to be very rare and delayed consequences of subdural collections, SDHys can apparently develop delayed or rapidly.…”
Section: Differential Diagnoses Of Subdural Hygromasmentioning
confidence: 99%
“…The suggested process describes the conversion of acute SDH into cSDH via SDHy as an intermediate stage (blue pathway in Fig 2). 47,66 Because most acute SDHs resolve rapidly, reflecting the high levels of tissue thromboplastin in brain tissue and CSF, 67 this approach has been refined by other authors. During the dissolving of the acute SDH, especially if decreased intracranial pressure is present, the cleaved dura-arachnoid interface is assumed to remain as persistent posttraumatic space.…”
Section: Concept 1: Delayed Formation Of Subdural Hygromasmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports lack a uniform approach to method and segment time [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Some authors have reported traumatic subdural hygroma presenting density modifications in the CT scan with change to chronic subdural hematoma 4,7,9,10,12,13,[15][16][17][18] . This study reports a series of South American adult patients with traumatic subdural hygroma, with emphasis on the evolution of clinical and CT scan data.…”
mentioning
confidence: 99%